Radiation Dosimetry and Biodistribution of 68Ga-FAPI-46 PET Imaging in Cancer Patients - Meyer, Catherine; Dahlbom, Magnus; Lindner, Thomas; Vauclin, Sebastien; Mona, Christine; Slavik, Roger; Czernin, Johannes; Haberkorn, Uwe; Calais, Jeremie (The Journal of nuclear medicine (1978), 2020)
Targeting cancer-associated fibroblasts (CAFs) has become an attractive goal for diagnostic imaging and therapy because they can constitute as much as 90% of a tumor mass. The serine protease fibroblast activation protein (FAP) is overexpressed selectively in CAFs, drawing interest in FAP as a stromal target. The quinoline-based FAP inhibitor (FAPI) PET tracer 68Ga-FAPI-04 has been previously shown to yield high tumor-to-background ratios (TBRs) in patients with various cancers. Recent developments toward an improved compound for therapeutic application have identified FAPI-46 as a promising agent because of an increased tumor retention time in comparison with FAPI-04. Here, we present a PET biodistribution and radiation dosimetry study of 68Ga-FAPI-46 in cancer patients. Methods: Six patients with different cancers underwent serial 68Ga-FAPI-46 PET/CT scans at 3 time points after radiotracer injection: 10 min, 1 h, and 3 h. The source organs consisted of the kidneys, bladder, liver, heart, spleen, bone marrow, uterus, and remainder of body. OLINDA/EXM software, version 1.1, was used to fit and integrate the kinetic organ activity data to yield total-body and organ time-integrated activity coefficients and residence times and, finally, organ-absorbed doses. SUVs and TBR were generated from the contoured tumor and source-organ volumes. Spheric volumes in muscle and blood pool were also obtained for TBR (tumor SUVmax/organ SUVmean). Results: At all time points, average SUVmax was highest in the liver. Tumor and organ SUVmean decreased over time, whereas TBRs in all organs but the uterus increased. The organs with the highest effective doses were bladder wall (2.41E−03 mSv/MBq), followed by ovaries (1.15E−03 mSv/MBq) and red marrow (8.49E−04 mSv/MBq). The average effective total-body dose was 7.80E−03 mSv/MBq. Conclusion: 68Ga-FAPI-46 PET/CT has a favorable dosimetry profile, with an estimated whole-body dose of 5.3 mSv for an administration of 200 MBq (5.4 mCi) of 68Ga-FAPI-46 (1.56 ± 0.26 mSv from the PET tracer and 3.7 mSv from 1 low-dose CT scan). The biodistribution study showed high TBRs increasing over time, suggesting high diagnostic performance and favorable tracer kinetics for potential therapeutic applications.